Pengembangan E-LKPD Berbasis Media Canva Untuk Meningkatkan Kemampuan Berpikir Kritis Pada Mata Pelajaran Pendidikan Pancasila Siswa Kelas V Sekolah Dasar - Aqilah Salsabila; Jamaluddin Arifin; Muhajir Muhajir (Jurnal Ilmiah Global Education, 2026)
This study aims to describe the characteristics of LKPD used in schools, design a conceptual design of Canva-based E-LKPD, and test the level of validity, practicality, and effectiveness of Canva-based E-LKPD in improving the critical thinking skills of fifth-grade students in the Pancasila Education subject. The study was conducted at SDN 53 Banyorang using the Research and Development (R&D) method through the ADDIE development model which includes the stages of analysis, design, development, implementation, and evaluation. Data collection was carried out using validation instruments from material experts and media experts, observation sheets, teacher response questionnaires, student response questionnaires, and critical thinking ability tests. The results of the study showed that the resulting product was a Canva-based E-LKPD on the material "Norms in My Life" in the Pancasila Education subject. The E-LKPD was declared very valid by material experts with a percentage of 91.75% and by media experts at 91.32%. The product was also declared very practical based on teacher responses with a percentage of 96.57% and student responses with an average of 95.27%. In terms of effectiveness, Canva-based E-LKPD media has been proven to be able to improve students' critical thinking skills as indicated by an increase in the average pretest score from 43.66% to 85.61% in the posttest, with an N-Gain value of 0.74 in the high category, and the results of the paired sample t-test showed a significant difference (t = -17.181; p < 0.001). These results indicate that Canva-based E-LKPD media is suitable for use as a digital teaching material in Pancasila Education learning in elementary schools.